Porównanie naturalnego odnowienia świerka pospolitego Picea abies (L.) Karst. na Pojezierzu Kaszubskim i w innych regionach północnej Polski - Szydlarski, Marcin; Majewski, Michał; Maras, Krzysztof; Modrzyński, Jerzy; Stopiński, Mateusz (Leśne Prace Badawcze, 2017)
The paper investigates the biometric characteristics natural Norway spruce ( Picea abies (L.) Karst.) regeneration in the Kaszuby Lake District, which is beyond the acknowledged Norway spruce range, with the natural regeneration in the Augustów Forest situated deep within the natural range, Warmia, at the edge of the natural range and in the West-Pomerania Lake District far beyond the natural range. For each region, four tree stands with similar light conditions on the forest floor were selected, including two cambisols and two brunic arenosols. All sites contained naturally regenerating spruces 16-17 years of age. The features of the forest stand and the biometric features of the saplings were determined for the selected stands on circular research plots. Altogether, the characteristicts of 400 saplings (100 in each region) were measured and analyzed using basic descriptive statistics. ANOVA with the Tukey’s multiple comparison test was performed to compare the features of forest stands and the natural regeneration of spruce in each region. The degree of interrelation between regeneration features was described by Pearson’s ,,r” factor or Spearman’s rank correlation coefficient. A discriminatory analysis was carried out to determine the set of regeneration features differentiating regions from each other. The features of regeneration that differed between regions the most were: height of regeneration, basal diameter, mean height increment, and mean basal diameter increment of the saplings. The parameters for Warmia and the West-Pomerania Lake District were similar. The Augustów Forest showed the lowest values for the regeneration parameters, while the Kaszuby Lake District produced the highest values. The regeneration in the Kaszuby Lake District was markedly different from all other regions as indicated by more dynamic growth. Additionally, this population shows a great distinctness, indicating adaptation to local environmental conditions, which may be proof for the insular presence hypothesis of spruce in this region. Due to their good quality, spontaneously developing natural regenerations in the Kaszuby Lake District should be supported by appropriate cutting and silvicultural measures.